ASSESSMENT OF ANTI-OBESITY ACTIVITY OF TECTONA GRANDIS LEAVES ON BUTTER INDUCED HYPERLIPIDEMIA IN MICE - PRASANNA, JAKKA LAKSHMI; RAO, NAKKA MADHAVA; KUMAR REDDY, BADDIGAM VENKATA SAI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Introduction: Obesity is one of the world’s leading problems, which is major cause of cardiovascular diseases. During COVID-19 pandemic many young children and all age group people are getting challenged by obesity due stagnant life style. To treat such life-threatening disorder natural remedies acquire prior position, plant produces a good deal of secondary metabolites which have a benefited mankind in various ways, including treatment of diseases. The present research work was focused on developing a natural remedy using Tectona grandis, an ancient plant with number of proven activities in traditional medicine. Methods: In the literature survey, it was found that flavonoids, sterols, tannins, and alkaloids shown promising effects to tackle obesity by various mechanisms, T. grandis has shown the presence of saponins, alkaloids, flavonoids, proteins, and amino acids. With the above evidence, this plant has been selected for screening of its antiobesity activity against high-fat diet induced obesity in mice. Studies were conducted using aqueous extract of T. grandis leaves (AETG) on high-fat diet (butter) induced model of hyperlipidemia in mice. During 21 days’ time period AETI low and high doses were induced to respective animal groups along with butter where atorvastatin has been taken as standard drug. Butter enhanced the cholesterol and triglyceride, low-density lipoprotein (LDL) levels. Results and Discussion: At the end of 21 days, blood samples were collected from the animal through retroperitoneal route. Biochemical parameters of AETG have been compared with that of standard drug group of animals. The test results were almost similar and for some particular parameters such as LDL and very low-density lipoprotein, AETG shown good results than standard drug results. Conclusion: In congruence with these results, it may be confirmed that due to the presence of phytoconstituents such as saponins, flavonoids, proteins, terpenoids, amino acids, and alkaloids in the aqueous extract of T. grandis, it could be responsible for the observed significant anti-obesity activity.